2000
DOI: 10.1038/sj.ejhg.5200546
|View full text |Cite
|
Sign up to set email alerts
|

A refined physical and transcriptional map of the SPG9 locus on 10q23.3–q24.2

Abstract: Hereditary spastic paraplegia (HSP) is a genetically heterogeneous disorder characterised by progressive spasticity of the lower limbs. Beside 'pure' forms of HSP, 'complicated' forms are reported, where spasticity occurs associated with additional symptoms. We recently described an Italian family with a complicated dominant form of HSP (SPG9) and we mapped the gene responsible to 10q23.3-q24.2, in a 12 cM interval between markers D10S564 and D10S603. The phenotypic manifestations in our family are reminiscent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
(19 reference statements)
1
15
0
Order By: Relevance
“…Aetiology: the mutated gene has not yet been detected but linkage analysis located the mutated gene to chromosome 10q23.3-24.1 [69].…”
Section: Spg9mentioning
confidence: 98%
See 1 more Smart Citation
“…Aetiology: the mutated gene has not yet been detected but linkage analysis located the mutated gene to chromosome 10q23.3-24.1 [69].…”
Section: Spg9mentioning
confidence: 98%
“…Clinical presentation: SPG9 represents a complex SPG with cataracts, gastro-esophageal reflux, and motor PNP in addition to "pure" manifestations [69].…”
Section: Spg9mentioning
confidence: 99%
“…10 It has been suggested that the syndrome described in the two families is genetically homogeneous. 9 Furthermore, a family with HSP and epilepsy was excluded for linkage to the SPG9 locus, which overlapped a partial epilepsy locus.…”
Section: Ann Neurol 2004;56:579 -582mentioning
confidence: 99%
“…8 The critical disease interval of 12cM (Ϸ9.2Mb) was slightly refined to approximately 7Mb when a second family with a motor system disorder linked to the SPG9 locus. 8,9 In addition to the motor system feature, this British family presented with bilateral cataracts, short stature, learning difficulties, muscle weakness, skeletal abnormalities, and anticipation. 10 It has been suggested that the syndrome described in the two families is genetically homogeneous.…”
mentioning
confidence: 99%
See 1 more Smart Citation